76.4k views
3 votes
Solve for x. 6x - 5x + 12 = 9 - 9x + 13 *

2 points
x = 0
x = 1
x = -1
none of the above

Solve the inequality. 5x + 11 > 2x + 38 *
2 points
x > 9
x -9
x 36 *
2 points
x > -3
x > 3
x < 3
x < -3

Solve for x. -5(3x + 8) = 20 *
2 points
x = 4
x = -30
x = -4
x = 4/3

multiple questions. i appreciate any help. thank you

1 Answer

4 votes

Answer:

x + 12 = 22 - 9x

x = 10 - 9x

10x = 10

x = 1

5x + 11 > 2x + 38

3x + 11 > 38

3x = 27

x = 9

15x - 40 = 20

-15x = 60

-x = 4

x = -4

User Journeycorner
by
4.8k points